Risk factors for hospital-associated venous thromboembolism in critically ill children following cardiothoracic surgery or therapeutic cardiac catheterisation. (8th November 2017) - Atchison, Christie M.; Amankwah, Ernest; Wilhelm, Jean; Arlikar, Shilpa; Branchford, Brian R.; Stock, Arabela; Streiff, Michael; Takemoto, Clifford; Ayala, Irmel; Everett, Allen; Stapleton, Gary; Jacobs, Marshall L.; et al.
Abstract: Background: Paediatric hospital-associated venous thromboembolism is a leading quality and safety concern at children's hospitals. Objective: The aim of this study was to determine risk factors for hospital-associated venous thromboembolism in critically ill children following cardiothoracic surgery or therapeutic cardiac catheterisation. Methods: We conducted a retrospective, case–control study of children admitted to the cardiovascular intensive care unit at Johns Hopkins All Children's Hospital (St. Petersburg, Florida, United States of America) from 2006 to 2013. Hospital-associated venous thromboembolism cases were identified based on ICD-9 discharge codes and validated using radiological record review. We randomly selected two contemporaneous cardiovascular intensive care unit controls without hospital-associated venous thromboembolism for each hospital-associated venous thromboembolism case, and limited the study population to patients who had undergone cardiothoracic surgery or therapeutic cardiac catheterisation. Odds ratios and 95% confidence intervals for associations between putative risk factors and hospital-associated venous thromboembolism were determined using univariate and multivariate logistic regression. Results: Among 2718 admissions to the cardiovascular intensive care unit during the study period, 65 met the criteria for hospital-associated venous thromboembolism (occurrence rate, 2%). Restriction to cases and controls having undergone the procedures of interest yielded a final study population of 57 hospital-associated venous thromboembolism cases and 76 controls. In a multiple logistic regression model, major infection (odds ratio=5.77, 95% confidence interval=1.06–31.4), age ⩽1 year (odds ratio=6.75, 95% confidence interval=1.13–160), and central venous catheterisation (odds ratio=7.36, 95% confidence interval=1.13–47.8) were found to be statistically significant independent risk factors for hospital-associated venous thromboembolism in these children. Patients with all three factors had a markedly increased post-test probability of having hospital-associated venous thromboembolism. Conclusion: Major infection, infancy, and central venous catheterisation are independent risk factors for hospital-associated venous thromboembolism in critically ill children following cardiothoracic surgery or cardiac catheter-based intervention, which, in combination, define a high-risk group for hospital-associated venous thromboembolism.